A gain-of-function sodium channel β2-subunit mutation in painful diabetic neuropathy. (May 2019) - Alsaloum, Matthew; Estacion, Mark; Almomani, Rowida; Gerrits, Monique M; Bönhof, Gidon J; Ziegler, Dan; Malik, Rayaz; Ferdousi, Maryam; Lauria, Giuseppe; Merkies, Ingemar SJ; Faber, Catharina G; Dib-Hajj, Sulayman; et al.
Diabetes mellitus is a global challenge with many diverse health sequelae, of which diabetic peripheral neuropathy is one of the most common. A substantial number of patients with diabetic peripheral neuropathy develop chronic pain, but the genetic and epigenetic factors that predispose diabetic peripheral neuropathy patients to develop neuropathic pain are poorly understood. Recent targeted genetic studies have identified mutations in α-subunits of voltage-gated sodium channels (Nav s) in patients with painful diabetic peripheral neuropathy. Mutations in proteins that regulate trafficking or functional properties of Nav s could expand the spectrum of patients with Nav -related peripheral neuropathies. The auxiliary sodium channel β-subunits (β1–4) have been reported to increase current density, alter inactivation kinetics, and modulate subcellular localization of Nav . Mutations in β-subunits have been associated with several diseases, including epilepsy, cancer, and diseases of the cardiac conducting system. However, mutations in β-subunits have never been shown previously to contribute to neuropathic pain. We report here a patient with painful diabetic peripheral neuropathy and negative genetic screening for mutations in SCN9A, SCN10A, and SCN11A —genes encoding sodium channel α-subunit that have been previously linked to the development of neuropathic pain. Genetic analysis revealed an aspartic acid to asparagine mutation, D109N, in the β2-subunit. Functional analysis using current-clamp revealed that the β2-D109N rendered dorsal root ganglion neurons hyperexcitable, especially in response to repetitive stimulation. Underlying the hyperexcitability induced by the β2-subunit mutation, as evidenced by voltage-clamp analysis, we found a depolarizing shift in the voltage dependence of Nav 1.7 fast inactivation and reduced use-dependent inhibition of the Nav 1.7 channel.